CEGAH STUNTING UNTUK MENINGKATKAN GENERASI EMAS DESA POMAHAN, KECAMATAN PULUNG, KABUPATEN PONOROGO (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
According to the data of the BKKBN East Java Province in 2018 Ponorogo is one of 11 regions that have become the focus of stunting. based on the observations we made, limited ANC services - Ante Natal Care (health services for mothers during pregnancy) Post Natal Care; lack of knowledge of local mothers regarding health and nutrition before and during pregnancy and after giving birth; lack of knowledge of the local community regarding stunting. The high number of jobs as migrant workers (Women Labor) carried out by mothers in Pomahan Village causes children at risk of suffering from stunting. This is because mothers are busy working so that the attention gained by children is also reduced, including the diet of children. With this edu